(untitled) (Conference Zone, 2022)
Any science has its own research methods. Through these methods, he enriches and updates his content. In life and in the theory of knowledge of the objective world, there are issues of what to teach and how to teach, who should be educated, and they are interrelated. learns with methods that are in accordance with its goals and tasks. In this article, thoughts and comments are made about the use of scientific research methods of pedagogy.